Experimental Investigation on Impact of Reynolds Number, Fitting Distance and Relative Diameter on Flow Separation around Piggyback Pipelines - Habib Hakimzadeh (نشریه مهندسی دریا, 2016)
In this paper, flow separations at downstream of piggyback pipelines due to the steady current have experimentally been investigated for various Reynolds numbers, gap ratios and relative diameters of the two pipes. A number of experiments including 6 verification tests and 50 main tests were conducted in a channel with length of 10m, width of 0.3m and 0.5m depth using Teflon rods (PTFE) with different diameters. To visualize the separation pattern, the polystyrene particles with a density of 1.05gr/cm3 have been used and the whole processes of tests have been recorded using a digital camera. The experimental results have shown that with adding the secondary pipe stuck to the main pipe, the symmetrical separation pattern vanished and its length reduced up to 60%. Also, it was observed that with increasing the gap ratio to a certain extent, the separation lengths increased and decreased gradually for the main and secondary pipes, respectively. However, further increase in the gap ratio showed that the two pipes behaved separately and the separation or recirculation patterns became symmetrical and their effect to each other became negligible.